BEBERAPA MASALAH DALAM PENGIMPLEMENTASIAN KEWAJIBAN NEGARA INDONESIA DI BAWAH PERJANJIAN INTERNASIONAL KE DALAM HUKUM NASIONAL INDONESIA - Parthiana, I Wayan (Veritas et Justitia, 2017)
Indonesia had been involved in the making of quite a number of international treaties and had also ratified a certain number of treaties. The State’s international obligations and rights stipulated by those treaties at a certain point must be implemented by and through the national legal system. Two issues identified are how to situate or place international treaties within the hierarchal order of the Indonesian legislation and, secondly, how those international rights and obligations (as found in treaties) should be harmonized (and incorporated) into the national legal system. The author shall present a general overview of those issues and offer some recommendations for change.